Efektivitas Google Classroom dalam Meningkatkan Pemahaman Siswa pada Pembelajaran IPA di SD Muhammadiyah MBS Prambanan - Ika Maryani; Amikratunnisyah Amikratunnisyah (N A T U R A L: Jurnal Ilmiah Pendidikan IPA, 2022)
Comprehension is a person's ability to understand something and interpret concepts that have been known or obtained previously. Google Classroom is a learning application created by Google to help educators and students do distance learning. This study aims to determine the effectiveness of google classroom in improving students' understanding of science learning at SD Muhammadiyah MBS Prambanan. The research method used was quasy experimental with a pretest-posttest only control group research design. Sampling was done by saturated sampling technique. The first sample is all students of class IV C totaling 16 students as the control class, and the second sample is all students of class IV D totaling 16 students as the experimental class. The results of the analysis show that there is no significant difference to online learning using google classroom with direct learning (conventional). This is shown from the results of the independent sample test where the sig. (2-tailed) 0.121> 0.05, which means that Ho is accepted and H1 is rejected. Whereas in the paired sample test, the sig value was obtained. (2-tailed) of 0,000 then H0 is rejected and H1 is accepted, which means that there is a mean difference between the pretest and posttest in the experimental class and the control class. Based on these results it can be concluded that google classroom is effective in improving students' understanding of science learning at SD Muhammadiyah MBS Prambanan.